Temporal and structural genetic variation in reindeer (Rangifer tarandus) associated with the pastoral transition in Northwestern Siberia - Røed, Knut H.; Kvie, Kjersti; Losey, Robert J.; Kositsev, Pavel A.; Hufthammer, Anne; Dwyer, Mark J.; Goncharov, Vasiliy; Klokov, Konstantin B.; Arzyutov, Dmitry; Plekhanov, Andreĭ V.; Anderson, David George (Ecology and Evolution, 2020)
Funding Information NordForsk. Grant Number: 76915 ERC Advanced Grant. Grant Numbers: 295458, ESRC ES/, M011054/1 JPI HUMANOR ERC Starting Grant Peer reviewed